2001
DOI: 10.1542/peds.108.4.e71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single-Use Sterile Catheter for Each Void on the Frequency of Bacteriuria in Children With Neurogenic Bladder on Intermittent Catheterization for Bladder Emptying

Abstract: ABSTRACT. Objective. The frequency of bacteriuria is high in children with neurogenic bladder on intermittent catheterization for bladder emptying. In an effort to decrease bacteriuria, we examined whether the method of catheter care was responsible for the high rate of bacteriuria. For this, the frequency of bacteriuria was examined in the same patient on single-use sterile catheters and on reused clean catheters.Methods. A prospective, randomized, crossover trial was conducted with 10 patients who were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 20 publications
0
24
0
5
Order By: Relevance
“…In addition, we examined whether the method of catheter care was responsible for the high rate of bacteriuria. 4 We found that a single-use, sterile catheter for bladder-emptying did not decrease the frequency of bacteriuria when compared to reused clean catheters.…”
Section: Introductionmentioning
confidence: 66%
“…In addition, we examined whether the method of catheter care was responsible for the high rate of bacteriuria. 4 We found that a single-use, sterile catheter for bladder-emptying did not decrease the frequency of bacteriuria when compared to reused clean catheters.…”
Section: Introductionmentioning
confidence: 66%
“…In another study in 2001, the same researchers found no difference between the incidence of sUTI whether using a single sterile catheter or using a clean catheter reused for up to five times. 13 However the sample consisted of only 10 patients. In our hospital practice of reusing catheters for 1, 2 or even 3 weeks, the risk for sUTI is potentially increased.…”
Section: Discussionmentioning
confidence: 99%
“…(8) El CIL se utiliza para disminuir la presión intravesical y la administración de agentes anticolinérgicos, para tratar las contracciones inestables del detrusor, con el fin de preservar la función renal, por lo que se recomienda el inicio precoz del tratamiento (11, 12) Para la realización del CIL los padres deben ser entrenados, dado que el mismo requiere de un correcto lavado de manos, del lavado de la región perineal con agua y jabón e insertar un catéter vesical a través de la uretra, advirtiéndoseles que una vez que la salida de orina se detuvo, el paciente debe realizar maniobra de Valsalva o el padre una compresión suave del área suprapúbica antes de remover el catéter (13).…”
Section: Manejo De La Vejigaunclassified
“…La desventaja de dicho procedimiento es la posible inoculación de bacterias dentro de la vejiga (13) No se ha encontrado ventajas en la utilización de un catéter estéril para cada vaciamiento vesical, con respecto al CIL, procedimiento en el que se reutilizan los catéteres. Sin embargo, la utilización de catéteres estériles aumenta mucho el costo del tratamiento (13) La efectividad del CIL es menor cuando hay reflujo vesicoureteral , por lo que se agregan anticolinérgicos para disminuir la presión vesical durante el llenado.…”
Section: Manejo De La Vejigaunclassified
See 1 more Smart Citation